PRODUCTION OF SODIUM SILICATE FROM RICE HUSK ASH WITH REGULATORY SETS MAGNESIUM - yanatra budi pramana; M. Amin Pahlevi; Zhulianto Ashari; M. Fariz Effendi; Fibra Gilang Ramadhan (Tibuana, 2020)
Utilization of rice husks in Indonesia in general is still very limited. Utilization of silica contained in rice husk ash, which has been used, among others, in the manufacture of sodium silicate. Silica compounds themselves can be used in and manufacturing basic materials for electronic and ceramic equipment, glass, rubber, cosmetic products, and pharmaceuticals. The addition of Mg can increase the silica content (SiO2) in rice husk ash. The best results show an effective Mg ratio of Mg addition to increase silica content is 1: 1. produces the highest amount of silica which is 58.12% of the rice husk ash with a size of 140 mesh